Integrating Educational and Psychological Perspectives in the Revitalization of Character Values in Madrasah: An Interdisciplinary Review - Maulida, Aulia Farkhatul; Tasrif, Moh.; Yuliani, Luluk; Baihaqi, Muhammad Hakam (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
The moral crisis among students, particularly in Islamic education, has become a significant concern due to rapid technological advancement, globalization, and shifting social values that challenge the internalization of akhlaq. This study aims to examine the integration of educational and psychological perspectives in revitalizing character values within madrasah education. This research employs a Systematic Literature Review (SLR) using a structured process of identification, screening, and analysis of relevant studies. The findings indicate that integrating educational and psychological approaches supports the holistic development of students’ moral, emotional, social, and spiritual dimensions. The incorporation of Islamic values (akhlaq), the role of teachers as moral exemplars (uswah hasanah), and collaboration among schools, families, and communities contribute significantly to strengthening students’ moral resilience and psychological well-being. However, this study is limited by its reliance on secondary data and the lack of empirical validation. Therefore, future research is recommended to conduct empirical and longitudinal studies to further examine the effectiveness of integrated models in Islamic educational contexts.